Model Pelatihan Kewiraswastaan Bidang Jasa Keterampilan Otomotif - Kusumah, Inu H. (INVOTEC, 2011)
The title of the research is â€œThe Model of Entrepreneurship Training for Automotive Vocational Skillsâ€.The approach of this research is research and development, in which the main approach is qualitative that is complemented with the quantitative approach in order to obtain the preliminary exploration data. The instruments of research are questionnaire, interview, observation and test. The findings of research indicate as in the follow:The causes of the juvenile dropped out of school are the factors of the: (a) juvenile psychological, (b) economic of family, and (c) environment where they live. The development of conceptual model to solve the problems of juvenile dropped out of school can be designed by using the approach ofÂ  needs assessment analysis for training. The activities are required in the development of conceptual model are: (a) recruitment of trainee candidates, (b) determination the hypothesis of competency, (c) scheduling, (d) facilities and area/(building for training), and (d) implementation and program evaluation.The empirical model was developed based on the conceptual model through the validation, analysis, and shared agreement among the researcher, community learning centre (PKBM), university, entrepreneurs and training specialists.The finding of try-out and implementation of empirical model of entrepreneurship training for automotive vocational skills indicated the availability aim and objective achievement; and thatâ€™s why it can be stated that the empirical model is effective.